Peran Penyuluh Agama dalam Membentuk Kesadaran Diri Remaja di Timur Indah RT.22 RW.02 - Sopia Fitria, Desy; Puspita Sari, Wiwied; Lestari, Mopi; Yolanda Pracella, Aisha; Zubaidah, Zubaidah (Yayasan Darussalam Bengkulu, 2024)
The role of religious instructors in the formation of awareness of adolescent self-diversity in Timur Indah RT.22 RW.02. Currently there are several cases that are reflected in the low level of religious awareness in some adolescents in Indonesia, Religious Counselors have a role in increasing religious awareness in adolescents who are the target group of Religious Counselors. The purpose of this study is to find out how the role and function of Religious Counselors in increasing the religious awareness of adolescents, the religious conditions of adolescents, and the sustainability of religious counseling activities in Timur Indah RT.22 RW.02. The method used is qualitative with a descriptive approach of phenomenology type. The technique in determining informants uses purposive sampling technique. The results of this study indicate that the roles and functions of Religious Counselors in Timur Indah RT.22 RW.02 carry out roles in participatory organizing, planning extension programs, identifying target problems and carrying out the duties and functions of the Religious Counselor itself based on the Decree of the Minister of Religion (KMA) Number 79 of 1985. The educative, informative and consultative functions are the dominant tasks carried out in Timur Indah RT.22 RW.02, teenagers have different religious awareness before and after joining Timur Indah RT.22 RW.02, religious counseling is carried out using lecture, question and answer and practice methods if needed, the output and outcom of the counseling can increase religious awareness which can indirectly affect the personal and social life of adolescents in the environment.